Transseptal antegrade transcatheter aortic valve replacement in a patient with severe aortic stenosis: a case report - A. V. Mikhailov; D. D. Zubarev; V. S. Krasnov; M. A. Chernyavsky; A. A. Prokhorikhin (Кардиоваскулярная терапия и профилактика)
We described a case report of transcatheter aortic valve replacement in conditions when the aortic stenosis anatomy does not make it possible to perform retrograde left ventricular catheterization, and the patient’s condition severity does not allow performing transapical or surgical aortic valve replacement. The presented technique of interatrial septal puncture with antegrade passage of the guidewire through the mitral and aortic valves and the venoarterial looping demonstrates an elegant way to solve this clinical situation, and can be adopted by specialists performing transcatheter interventions in severe aortic stenosis.